Hubungan Pembiayaan Kesehatan Dengan Tingkat Kepatuhan Pasien Hipertensi Dalam Menjalani Pengobatan - Hanifa, Ummu; Karim, Darwin; Woferst, Rismadefi (Universitas Pahlawan Tuanku Tambusai, 2024)
Hypertension is also known as the silent killer because patients are often unaware that they have hypertension until they check their blood pressure. Hypertension is a disease that cannot be cured but must be controlled. Patient compliance in undergoing treatment is crucial to achieve optimal blood pressure control and prevent serious complications. However, several factors affect compliance, one of which is cost. The role of cost can impact various aspects, including access to care, adherence to medication, and the financial burden on patients. Purpose of this research is to understand the relationship between health financing and the adherence level of hypertensive patients in undergoing treatment. Method the research utilized a descriptive correlational study design with a cross-sectional approach. The population for this study consisted of hypertension patients undergoing treatment at RSUD Arifin Achmad, with a sample size of 85 respondents selected through purposive sampling techniques. Based on the data analysis conducted using the chi-square test, a p-value of 0.001 < 0.05, indicating that there is a significant relationship. The conclusion there is a relationship between health financing and the level of compliance of hypertension patients in undergoing.